2009
DOI: 10.1111/j.1468-3083.2009.03259.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual, right-left comparison of topical 5-aminolevulinic acid photodynamic therapy vs. 5% imiquimod cream for actinic keratoses on the upper extremities

Abstract: Our study shows that ALA-PDT and 5% IMIQ cream are both attractive treatment options for upper extremities AKs with comparable efficacy and cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 21 publications
1
73
1
Order By: Relevance
“…18,19 Published studies have demonstrated high clearance rates with multiple topical PDT regimens that are comparable with other topical therapies used for the treatment of AKs, particularly on the face and scalp. 8,9,20 However, the efficacy of PDT on the extremities is greatly reduced. 1,2,10,21,22 The strong relationship between temperature and porphyrin synthesis in biologic tissue [23][24][25][26][27][28] suggests that increasing the temperature of the skin during the incubation of ALA may improve the efficacy of PDT, particularly for areas that are naturally lower in temperature such as the distal extremities.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…18,19 Published studies have demonstrated high clearance rates with multiple topical PDT regimens that are comparable with other topical therapies used for the treatment of AKs, particularly on the face and scalp. 8,9,20 However, the efficacy of PDT on the extremities is greatly reduced. 1,2,10,21,22 The strong relationship between temperature and porphyrin synthesis in biologic tissue [23][24][25][26][27][28] suggests that increasing the temperature of the skin during the incubation of ALA may improve the efficacy of PDT, particularly for areas that are naturally lower in temperature such as the distal extremities.…”
Section: Resultsmentioning
confidence: 98%
“…8,9,20 Warming the skin within the threshold of thermal tolerability was well tolerated by subjects, despite moderate increases in stinging during light exposure and increased PDT skin reactions after treatment. A long-term follow-up study is currently underway to evaluate the longevity of AK clearance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite this pretreatment, thicker AKs respond at a reduced rate and may require more treatment sessions to achieve clearance. 22,61,39 PDT does not effect a full reversal of photodamage in all instances; AKs may begin to emerge after 4 to 6 months. 18,62 In patients with a history of NMSC, 2 sessions of ALA-PDT delayed the emergence of AKs and other lesions from severely photodamaged skin, relative to placebo treatment.…”
Section: Pdt and Daylight Pdtmentioning
confidence: 99%
“…AK research is singularly well suited to intraindividual comparison studies-for example, split-face or split-scalp studies, in which different therapies are used to treat otherwise-identical areas of photodamaged skin. 22,26,[32][33][34] Efficacy outcomes differ across studies in the AK literature, making comparisons difficult. In particular, some studies report the proportion of lesions that respond to treatment, whereas others report the rate of complete clearance within the treatment field.…”
Section: Overview Of the Clinical Literature On Aksmentioning
confidence: 99%